Preparing and delivering scientific presentations a complete guide for international medical scientists - Giba, John (Springer, 2011)
The latest in Springer's "Medical English" series aimed at healthcare professionals who need English for their work but do not speak English on a day-to-day basis, this book features clear advice on a variety of topics relevant to the successful preparation and delivery of scientific presentations. It also covers a wide range of situations that may develop in the context of an international congress and includes specific chapters on important issues like dealing with questions, chairing sessions, and avoiding common pitfalls in English usage and pronunciation. Although much of the information provided will be useful for scientists of all backgrounds and nationalities, the book is aimed especially at non-native English-speaking physicians and biomedical scientists. It will be an invaluable addition to the libraries of experienced presenters as well as of those just beginning their careers in international science.